THE FALSIFICATION OF CATHOLIC NEWSPAPER O SÃO PAULO: AN ANALYSIS OF THE MEDIATIC REACTION TO MEA CULPA EDITION (1982) - Lanza, Fabio; Neves Júnior, José Wilson Assis [UNESP]; Rodrigues, Raíssa Regina Brugiato (Pontifical Catholic University of Sao Paulo (PUC-SP), 2020)
This paper analyzes the falsification process of one edition of the catholic newspaper O São Paulo (1982). Focuses on mediatic reaction posterior to the fact, that generated 154 documents from magazines and newspapers. Were utilized the documental analysis, with contributions from discourse analysis, under the historical-processual perspective of Karl Mannheim and Norbert Elias matrix. The intention, of the group responsible for the falsification, to manipulated the newspaper lectors for vigilance and rejection to “communists” was apprehended, the mediatic reaction evidenced the attempted to retrench the possibilities to express distinguish perspectives of Brazilian military dictatorship social-political reality.
A FALSIFICAÇÃO DO JORNAL CATÓLICO O SÃO PAULO: UMA ANÁLISE DA REAÇÃO MIDIÁTICA À EDIÇÃO MEA CULPA (1982)
Keywords: Catholic newspaper O São Paulo; Conservative Thought; Media Reaction; Military Dictatorship (1964-1985)